THE INFLUENCE OF TECHNOSTRESS ON JOB PERFORMANCE AMONG TEACHERS: MODERATING ROLE OF AUTHORITARIAN LEADERSHIP AND BOSS PHUBBING - Ahmad Syahmi Bin Ahmad Fadzil; Muhammad Bin Majid; Mohamad Haniff Bin Mohd Yasin (International Journal of Accounting, Finance and Business, 2023)
Almost every job sector in this world are depending on Information, Communication and Technology (ICT) including the academic sector. Process of teaching, learning, research and administration using ICT are heavily dependent on the academic institution. Despite of ICT having many advantages, it can create Technostress among teachers when overuse, incompetence or fast-changing of ICT. Technostress can reduce job performance. This study intends to highlight the gap or the grey area of Technostress on job performance with the moderating role of authoritarian leadership and boss phubbing among school teachers. This study is intended to be conducted on rural primary and rural secondary school teachers around Segamat, Johor and use PLS-SEM to examine the associations among the variables. The early findings of this study show the proposed framework derived from past studies and anchored the framework through Transactional Theory of Stress. Additionally, the findings also highlighted the gap left by recent research. This research is hopeful to be conducted via primary data collection next to obtain more details and understanding on the associations among the variables involved.